Management of Extracranial Carotid Artery Aneurysm. Issue 2 (August 2015) - Welleweerd, J.C.; den Ruijter, H.M.; Nelissen, B.G.L.; Bots, M.L.; Kappelle, L.J.; Rinkel, G.J.E.; Moll, F.L.; de Borst, G.J.
Abstract : Introduction: Aneurysms of the extracranial carotid artery (ECAA) are rare. Several treatments have been developed over the last 20 years, yet the preferred method to treat ECAA remains unknown. This paper is a review of all available literature on the risk of complications and long-term outcome after conservative or invasive treatment of patients with ECAA. Methods: Reports on ECAA treatment until July 2014 were searched in PubMed and Embase using the key words aneurysm, carotid, extracranial, and therapy. Results: A total of 281 articles were identified. Selected articles were case reports ( n = 179) or case series ( n = 102). Papers with fewer than 10 patients were excluded, resulting in the final selection of 39 articles covering a total of 1, 239 patients. Treatment consisted of either conservative treatment in 11% of the cases or invasive treatment in 89% of the cases. Invasive treatment comprised surgery in 94%, endovascular approach in 5%, and a hybrid approach in 1% of the patients. The most common complication described after invasive therapy was cranial nerve damage, which occurred in 11.8% of patients after surgery. The 30 day mortality rate and stroke rate in conservatively treated patients was 4.67% and 6.67%, after surgery 1.91% and 5.16%. Information on confounders in the present study was incomplete. Therefore, adjustments to correct for confounding by indication could not be done. Conclusions: This review summarizes the largest available series in the literature on ECAA management. The number of ECAAs reported in current literature is scarce. The early and long-term outcome of invasive treatment in ECAA is favorable; however, cranial nerve damage after surgery occurs frequently. Unfortunately, due to limitations in reporting of results and confounding by indication in the available literature, it was not possible to determine the optimal treatment strategy. There is a need for a multicenter international registry to reveal the optimal treatment for ECAA.